An Unusual Benign Cause of an Alarming Finding on Chest-X ray: A Case Report of Widened Mediastinum due to Rare Congenital Abnormality (Azygos Vein Continuation of Inferior Vena Cava). (9th December 2019) - Hanna, Michael; Elshimy, Ghada; Ismail, Medhat; Ismail, Mourad
Abstract : Acute widened mediastinum is an alarming finding. It has many possible differential diagnoses; aortic dissection (AD) is considered one that carries catastrophic outcomes. AD is relatively uncommon; it requires early and accurate diagnosis and treatment for better patient survival. However, acute mediastinal widening also can be present in more benign conditions. We report a case of a 50-year-old African American female with postoperative shortness of breath; initial imaging studies revealed an acute widened mediastinum, but on further management with diuresis and follow-up imaging, she was diagnosed with azygous vein continuation of the Inferior vena cava (IVC). This is considered as a rare benign cause of wide mediastinum. Clinicians must be aware of the presence of such a benign cause when dealing with acute wide mediastinum.